دور راس المال الفكري في تحقيق الميزة التنافسية للمصارف الإسلامية الأردنية: دراسة حالة البنك الإسلامي الأردني. - تيسير بطاينة, منار (جامعة الوادي - University of Eloued, 2020)
هدفت الدراسة لبيان دور راس المال الفكري في تحقيق الميزة التنافسية للمصارف الإسلامية في الأردن، وذلك من خلال دراسة حالة البنك الإسلامي الأردني، حيث تم تصميم استبانة بغرض تحقيق أهداف الدراسة والمتمثلة باختبار الفرضية الرئيسية للدراسة والمتمثلة بالسؤال التالي: هل توجد علاقة ذات دلالة إحصائية بين مدى توافر متطلبات رأس المال الفكري وتحقيق الميزة التنافسية للمصارف الإسلامية في الأردن، وقد توصلت الدراسة إلى أن جميع محاور راس المال الفكري إيجابية، أي أن البنك محل الدراسة لدية مستوى جيد من رأس المال الفكري، مع توفر متطلبات تحقيق رأس المال البشري ورأس المال الهيكلي ورأس مال العلاقات وكلها تحقق الميزة التنافسية له من خلال استغلال تلك الثروة الفكرية للبنك. وقد أوصت الدراسة ضرورة المحافظة على رأس المال الفكري باعتباره ثروة قيمة ومورد استراتيجي تمتلكها المؤسسات المصرفية حيث تساهم تلك الثروة في زيادة الحصة السوقية للمؤسسة المصرفية، والاهتمام بالدراسات والأبحاث المتعلقة برأس المال الفكري وبيان الطرق التي يمكن من خلالها استثمارية بطريقة صحيحة، ولابد من قيام المؤسسات المصرفية بإجراء تقييم دوري لمعرفة حجم رأس المال الفكري، وقياس دورة في تحقيق التميز في أعمال تلك المؤسسات. The study aimed at demonstrating the role of intellectual capital in achieving the competitive advantage of Islamic banks in Jordan, taking Jordan Islamic Bank as a case study. Therefore, a questionnaire was designed to answer the following question: Is there a statistically significant relationship between the availability of intellectual capital requirements and achieving the competitive advantage of Islamic banks in Jordan? The study concluded that all axes of intellectual capital are positive, this means that the bank under study has a good level of intellectual capital, as well as the requirements of achieving human capital, structural capital and capital relations. All of these requirements participate in achieving competitive advantages by employing the intellectual capacities of the bank. The study stressed the need to preserve intellectual capital as a valuable component and a strategic resource owned by banking institutions, which increases the market share of the banks. The study highlighted the value of studies and research related to intellectual capital and the ways to invest it. Finally, the study recommended that banking institutions should conduct a periodic assessment to evaluate its intellectual capital, and measure its role in achieving excellence.
Intellectual capital role in building the competitive features of Islamic banks: Jordan Islamic bank as a case study
مقال
Keywords: البنك الإسلامي الأردني ; راس المال البشري ; راس المال الفكري ; المصارف الإسلامية ; الميزة التنافسية